INCREASING SOCIAL STATUS OF WOMEN IN THE YEARS OF INDEPENDENCE (IN THE CASE OF SURKHANDARYA REGION) - Rajbova Sabohat Bobirovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In this article, in 1999-2004, opinions are given on the increase of the social status of women in the family and society and the legal protection of their labor. Resolution No. 117 of March 17, 1999, adopted by the Cabinet of Ministers